Visual outcomes in patients with meningiomas compressing optic nerve - Krahulik, David; Blazek, Filip; Hampl, Martin; Hrabalek, Lumir; Krahulik, Jan; Karhanova, Marta (Frontiers in Neurology, 2025)
BackgroundMeningiomas compressing the optic nerve can lead to progressive visual loss due to the nerve’s complex intraorbital, intracanalicular, and intracranial anatomy. Although observation, radiation, and surgical decompression are available, optimal strategies for preserving vision remain controversial. This study retrospectively evaluates the impact of surgical intervention on visual recovery in patients with optic nerve–compressing meningiomas to refine patient selection and treatment strategies.MethodsA retrospective review was conducted on medical records from the Neurosurgical Clinic at Olomouc University Hospital for patients undergoing surgical treatment for meningiomas near the optic nerve from 2015 to 2023. Inclusion criteria required high-quality preoperative and postoperative MRI, complete ophthalmic records, and a minimum one-year follow-up. Data on demographics, tumor characteristics (size, location, and relationship with the optic nerve), and visual function (acuity and field) were collected. Tumors were categorized by size and degree of optic nerve involvement, and visual outcomes were assessed pre- and postoperatively.ResultsSeventy-nine patients (66 females, 13 males; mean age 58) met inclusion criteria. A longer duration of visual impairment correlated with more severe preoperative vision loss. Although postoperative visual function did not significantly correlate with tumor size, location, or duration of preoperative symptoms, patients with shorter impairment durations demonstrated better postoperative recovery.ConclusionThe duration of preoperative visual impairment is a critical predictor of visual outcomes, supporting early surgical intervention for optic nerve–compressing meningiomas. While tumor size and location did not directly influence recovery, further investigation into tumor-anatomy relationships is warranted to optimize visual prognosis.